Editorial - Carrerete, Fabricio Borges (Brazilian Journal of Health and Biomedical Sciences, 2022)
In the next year, 2022, we are planning to return to our in-person activities. After a long period in remote work, this brings us great breath and hope for better days. Mass vaccination is a gold medal won despite many difficulties and obscure obstacles, in opposition to our principle of taking science above beliefs, empty opinions, without ambiguity, and fake news. This issue of our journal crowns this hopeful return with interesting articles such as the epidemiological study of hypertensive elderly people, risk factors associated with many morbidities including respiratory syndrome caused by viruses; association between smoking and COVID 19, a subject always highlighted by the current and importance of the topic; well-designed protocols for clinical studies with vibration exercises; infectious diseases in intensive care units, a matter of extreme relevance, given the exponential increase in these patients caused by the pandemic; in addition to studies in genetics and biochemistry, important analytical parameters in studies of cancer and metabolic alterations related to smoking, a great epidemic of our times. Finally, review articles with relevant topics in tropical infectious disease and cancer. We close with a clinical case to sharpen our reasoning and bring a light and stimulating learning experience. A good read for everyone, happy 2022.